2020
DOI: 10.1093/neuonc/noaa058
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic inhibition of lysine-specific demethylase 1 as a therapeutic and immune-sensitization strategy in pediatric high-grade glioma

Abstract: Background Diffuse midline gliomas (DMG), including brainstem diffuse intrinsic pontine glioma (DIPG), are incurable pediatric high-grade gliomas (pHGG). Mutations in the H3 histone tail (H3.1/3.3-K27M) are a feature of DIPG, rendering them therapeutically sensitive to small-molecule inhibition of chromatin modifiers. Pharmacological inhibition of lysine-specific demethylase 1 (LSD1) is clinically relevant but has not been carefully investigated in pHGG or DIPG. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 48 publications
2
38
0
Order By: Relevance
“…We next examined if NK cell sensitivity to scaffolding LSD1 inhibitors was dose and time dependent, and we found higher doses and longer incubation times amplified the cytotoxic effect ( Figure 1E, q < 0.001). Our previous publication also found metabolic suppression unique to scaffolding LSD1 inhibitors in NK cells (7). We were able to replicate these findings using numerous unique NK cell donors, observing that scaffolding LSD1 inhibitors abolish all oxidative phosphorylation in NK cells ( Figure 1F, * q < 0.01) and reduce OXPHOS to a much lesser degree in T-cells ( Figure 1G, * q < 0.01).…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations
“…We next examined if NK cell sensitivity to scaffolding LSD1 inhibitors was dose and time dependent, and we found higher doses and longer incubation times amplified the cytotoxic effect ( Figure 1E, q < 0.001). Our previous publication also found metabolic suppression unique to scaffolding LSD1 inhibitors in NK cells (7). We were able to replicate these findings using numerous unique NK cell donors, observing that scaffolding LSD1 inhibitors abolish all oxidative phosphorylation in NK cells ( Figure 1F, * q < 0.01) and reduce OXPHOS to a much lesser degree in T-cells ( Figure 1G, * q < 0.01).…”
Section: Resultssupporting
confidence: 76%
“…Our group has previously published that the scaffolding LSD1 inhibitor SP-2509 and its clinical successor SP-2577, or seclidemstat, potently suppress the viability and metabolism of NK cells (7). The NK cells in our previous report and this current study are expanded from healthy human donors into a cell therapy-grade product.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…A more expansive in vitro followed by in vivo screen of the combinatorial druggable DMG landscape, with clinically relevant factors such as potency and blood–brain-barrier penetrance taken into account, revealed the proteasome inhibitor marizomib combined with panobinostat as the most promising pairing [ 88 ]. Additional in vivo studies have suggested inhibition of lysine demethylase [ 89 , 90 ], DNA methylation [ 63 ], AXL kinase [ 91 ], and PI3K [ 92 ] as promising combination strategies with panobinostat, several of which are now in clinical trials.…”
Section: Development Of Novel Therapiesmentioning
confidence: 99%